Prevalence of Scheloribates, Berlese, 1908 and Galumna, Von Heyden 1826 and their infection with Moniesia spp. cysticercoids on pastures of Vologda region - A. L. Kryazhev; V. F. Nikitin (Российский паразитологический журнал)
Prevalence of ticks of the genius Scheloribates, Berlese, 1908 and Galumna, by von Heyden, 1826 and their infection with Moniesia spp. cysticercoids on vari-ous types of pastures of the Vologda region is studied. Density of population of ticks of the genius Scheloribates and Galumna made in the soil of shelters for ani-mals 714±47,0, natural forest pastures 312±31,0, natural meadow pastures 167±14,0, artificial cultural pastures 114±8,0, haymaking places under hay rolls 122±18,0 expl./m2 at detection of Moniesia spp. cysticercoids respectively at 50,1; 26,9; 22,8; 0 and 13,9 % ticks. The maximum number of ticks is revealed in July–August in shelters of summer camps for animal and natural forest and meadow pas-tures, and the smallest – on artificial cultural pastures. Animals in shelters for over-exposure are subject to the maximum risk of infection with moniesiosis.